2013
DOI: 10.1136/bmj.f1429
|View full text |Cite
|
Sign up to set email alerts
|

Increasing activity in patients with Parkinson's disease

Abstract: Crucially important but requires complex long term support

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Medical and surgical treatments for PD have often been monitored at the symptom or symptom-related quality of life level, for example, reference [28], but they can have broader impacts on participation. Some recent published trials and reviews of rehabilitation programs for PD have suggested the need for measurement of lived outcomes in a way that is not arduous for participants who may have cognitive and physical impairments [24,31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical and surgical treatments for PD have often been monitored at the symptom or symptom-related quality of life level, for example, reference [28], but they can have broader impacts on participation. Some recent published trials and reviews of rehabilitation programs for PD have suggested the need for measurement of lived outcomes in a way that is not arduous for participants who may have cognitive and physical impairments [24,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Interventions for people with PD can target safe outdoor mobility, confidence with mobility, and ease with leaving the home [23,24]. Lifespace therefore gives an opportunity to monitor the implications of the combined impact of the symptoms of PD, the available supports, and the impact on daily life.…”
Section: Introductionmentioning
confidence: 99%